Overview of financial inclusion, regulation, financial literacy, and education in Central Asia and South Caucasus - Peter J. Morgan; Yan Zhang; Dossym Kydyrbayev (Asian Development Bank Institute (ADBI), 2018)
Financial inclusion and financial literacy are receiving increasing attention for their potential to contribute to economic and financial development while fostering more inclusive growth and greater income equality. In general, the progress of financial inclusion and financial development in the economies in Central Asia and the South Caucasus (CASC) has lagged that of other Asian economies, partly due to the disruptions and instabilities following the breakup of the Soviet Union in 1991. The purpose of this study is to survey the experiences of the CASC economies to assess factors affecting the ability of low-income households and small and medium-sized firms to access financial services, including financial literacy, financial education programs, and financial regulatory frameworks, and to identify policies that can improve their financial access while maintaining financial stability. It aims to identify successful experiences and lessons that can be adopted by other emerging economies.
Keywords: G21; G28; I22; O16; O17; 330; financial inclusion; financial literacy; financial regulation; consumer protection; banks; microfinance; insurance; pensions; Armenia; Azerbaijan; Georgia; Kazakhstan; Kyrgyz Republic; Tajikistan; Uzbekistan; Central Asia; South Caucasus